CYSTIC ENDOMETRIAL HYPERPLASIA - OPEN PYOMETRA COMPLEX IN A FEMALE PUG - HAJI, M M; BORPUJARI, D; TALUKDAR, D J; AHMED, F A; LALRINTLUANGA, K; SARMA, K (The Indian Journal of Animal Reproduction, 2017)
A five-year old pug had the history of inappetance, polydipsia, occasional vomition and diarrhea. The vaginalexamination revealed brown chocolate malodorous discharge. The uterine ultrasound showed hyperplasia andmultiple distended circular hypoechoic and anechoic cysts filled with echogenic material in the uterine wall alongwith distended uterine horns containing large volume of cellular contents. Based upon ultrasonography, vaginalcytology and haemato-biochemcial picture, the animal was diagnosed with cystic endometrial hyperplasia (CEH)-open pyometra complex. The bitch was treated with synthetic prostaglandin analog, methyl ergometrine andceftriaxone. After one week, the bitch showed marked improvement with the absence of vaginal discharge,normal ultrasonographic report of uterus and normal haemato-biochemical picture. In conclusion, a syntheticprostaglandin analog along with methyl ergometrine can be used as the drug of choice for treating CEH-openpyometra complex without any adverse effect.
Keywords: Bitch; Cystic endometrial hyperplasia.; Pyometra; Therapy Ultrasonography